The Impact of Ownership Structure on Sustainable Performance Disclosure and Firm Value: An Empirical Study of State-Owned Enterprises in Indonesia (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2025)
Environmental sustainability has become an essential approach for companies to enhance their competitive advantage and reputation. This study examines the effect of ownership structure on sustainability performance and firm value. This study uses data from state-owned enterprises listed on the Indonesia Stock Exchange. Ownership structure is proxied by institutional ownership, management ownership, and public ownership; sustainability performance is proxied by the total economic score, environmental score, and social score; and firm value is proxied by Tobin's Q. Our results reveal that ownership structure (management ownership, institutional ownership, and public ownership) have a direct effect on firm value, but indirectly do not have an indirect effect on firm value through CSR does not mediate the relationship between management ownership and institutional ownership with firm value. The unique findings of this study indicate that CSR mediates the relationship between public ownership and firm value. Public ownership partially mediates the relationship between firm type and firm value. The implications of this study will be significant for policymakers, corporate management, academics, and investors in considering the adoption and importance of corporate environmental practices.